Rational Choice and Social Welfare Theory and Applications - Pattanaik, Prasanta K.; Tadenuma, Koichi; Xu, Yongsheng; Yoshihara, Naoki (Studies in Choice and Welfare, 2008)
The papers in this volume explore various issues relating to theories of rational choice and social welfare and their applications. The topics include resource allocation problems, population ethics, rationalizability of choice functions and demand functions for money, game theory, individual rights, and measurements of vulnerability, diversity, and changes in individual welfare. Researchers and advanced graduate students who want to learn more about such topics will find the book very useful.